Effects of the Coronavirus (COVID-19) Pandemic on Social Behaviours: From a Social Dilemma Perspective - Ling, Gabriel, H. T.; Ho, Christina Mee Chyong (Technium Social Sciences Journal, 2020)
The health crisis of the COVID-19 outbreak has global impacts on humanity and the economy. Such pandemic effects are believed to have influenced human behaviour; issues of panic buying (overbuying) and noncompliance among individuals are shown evident. However, the underlying understanding on such behaviours due to the pandemic remains unclear. Therefore, this perspective paper adopts the social dilemma theory and microeconomics concepts to analyse and explain the effects of COVID-19 on social behavioural reactions. It attempts to address the questions of what and why are the behaviours of individuals shown during the coronavirus pandemic and showcase how the theory is associated with current social phenomena. Real scenarios based on media reporting from the sociodemographic context of Malaysia, concerning the following issues; (i) competition over daily essentials; (ii) self-honesty of individuals; and (iii) adherence to government policies and measures enforcement (governance) were discussed. A conceptual framework was developed to illustrate interrelationships between social dilemma concepts and the phenomena. In essence, due to fear, uncertainty and greed, selfinterest and opportunistic (defective/unethical) behaviours of most individuals prevailing over societal collective interest amid the pandemic have been prevalently observed in the above instances, although a cooperative choice can eventually result in a better outcome for everyone. Not only do these non-cooperative behaviours of individuals create inconveniences, dissatisfactions and other forms of negative externalities, they also incentivise others to act selfishly, if no restrictions are imposed, that may eventually cause government interventions failures. This paper demonstrates the relevancy of the social dilemmas theory in better understanding fundamental human behavioural reactions amid the health crisis and the importance of incorporating the findings into government policymaking. These sociopsychological considerations help the government formulate holistic measures, namely stringent sanctions and monitoring enforcement, as well as incentivising cooperative and compliant behaviours of the public, which then contribute to curbing the COVID-19 pandemic more effectively.